The Effect of Earnings Quality and Dividend Policy on Firm Value : Evidence from PT Alkindo Naratama Tbk (2014–2024) - Anardia Destiyana; Jeni Irnawati (International Journal of Economics, Management and Accounting, 2026)
This study examines the influence of earnings quality and dividend policy on firm value at PT Alkindo Naratama Tbk during the period 2014–2024. Firm value is measured using the Price to Book Value (PBV), earnings quality is proxied by the ratio of operating cash flow to net income (QOE), and dividend policy is measured using the Dividend Payout Ratio (DPR). This research adopts a quantitative approach with an associative causal design using secondary data obtained from the company’s quarterly financial reports over eleven years, resulting in 44 observations. The analysis method applied is multiple linear regression. The findings reveal that earnings quality has a positive and significant impact on firm value. Dividend policy also shows a positive and significant effect on firm value. Simultaneously, earnings quality and dividend policy significantly influence firm value. The coefficient of determination indicates that a large proportion of firm value variation can be explained by these two variables. These results support signaling theory, which suggests that high earnings quality and stable dividend distribution provide positive signals to investors and increase market confidence in the company. The study contributes to financial management literature by highlighting the importance of financial performance indicators in determining firm value.